1992 Evaluation of Downstream Fish Passage Facilities at the West Enfield Hydroelectric Project - Bangor-Pacific Hydro Associates (ScholarWorks@UMass Amherst, 1993)
None suppled. From background: The redevelopment of the West Enfield Hydroelectric Project (FERC No. 2600-027) was completed in the Fall of 1988 by Bangor-Pacific Hydro Associates. The Federal Energy Regulatory Commission, by order dated June 27, 1987 and amended by orders dated April 16, 1990, June 11, 1991, and June 2, 1992, directed the licensee to evaluate the adequacy of the West Enfield Project upstream and downstream passage facilities. Only the passage of juvenile Atlantic salmon (smolt) was evaluated in this study. The smolt study focused on the project area but for practical purposes covered the entire main stem of the Penobscot from the release site to beyond the Veazie Dam 50 km downstream.